1984
DOI: 10.1073/pnas.81.6.1789
|View full text |Cite
|
Sign up to set email alerts
|

A genomic gene encoding the b5 rabbit immunoglobulin kappa constant region: implications for latent allotype phenomenon.

Abstract: We previously reported that domestic rabbits of five immunoglobulin K allotype strains (b4', b4, b5, b6, and b9) harbor at least two DNA sequences that hybridize strongly to K constant region probes in Southern blots. One of these sequences ("type A") has been identified as encoding the constant region of the K2 isotype, an immunoglobulin chain that most rabbits express only at low levels, if at all. We identified the second sequence-for rabbits of the b4 allotype-as encoding the nominal b4 K chain (or K1 isot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

1985
1985
1995
1995

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 21 publications
2
14
0
Order By: Relevance
“…The b4 and b5 genomic sequences differ in their coding regions (330 base pairs) by 39 base-pair substitutions at amino acid replacement sites for only four at synonymous sites, while 96% ofthe base pairs ofthe 3'-untranslated region are conserved (7)(8)(9). A somewhat similar situation exists for Ig C-region genes in other species (33,34).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…The b4 and b5 genomic sequences differ in their coding regions (330 base pairs) by 39 base-pair substitutions at amino acid replacement sites for only four at synonymous sites, while 96% ofthe base pairs ofthe 3'-untranslated region are conserved (7)(8)(9). A somewhat similar situation exists for Ig C-region genes in other species (33,34).…”
Section: Discussionmentioning
confidence: 76%
“…The different b-locus allotypes (b4, b5, b6, and b9) are associated with multiple amino acid differences throughout the C region of the K L chain. Although alleles can differ by up to 33% in amino acid sequence (6, 7), studies at the genome level have confirmed them as true alleles at a single gene locus (8,9). A most interesting finding was that the nucleotide sequences of b-locus alleles differ almost exclusively by base-pair substitutions causing amino acid replacements (7-9).…”
Section: Introductionmentioning
confidence: 83%
“…The N9 sequence was found to be identical to either the b95 sequence or to the sequence representing a nominal b6 allotype except for six nucleotide substitutions. Two of these substitutions convert an Eco RI Akimenko et al 1984Emorine et al 1983Emorine et al 1984Dreher et al 1990 Ayadi and site into a Bam HI site. The restriction fragment analysis confirmed that such a site is indeed present, not only in PCR products obtained with DNA from rabbit N9, but also in products derived from each of four other rabbits typed as b6w2 (see Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…There exists a high degree of C, polymorphism in rabbit, with allotypes b4, b5, b9, and bas-N4 common in domesticated populations. These allotypes were distinguished originally by serologic methods and recently by detection of multiple amino acid substitutions (15,16). The rabbit K complex embodies two isotypes.…”
Section: Analysis Section 1 C-domain Block Identitiesmentioning
confidence: 99%
“…1). The rabbit C, allotypes (b4, b5, b9, bas) feature an extraordinary degree of amino acid replacement (15,16). In fact, >40% of all nucleotide substitutions between these C, sequences are nonsynonymous.…”
mentioning
confidence: 99%